KONSTRUKSI BENTUK-BENTUK KOMUNIKASI DAN IDENTITAS DIRI KONTEN KREATOR PADA MEDIA SOSIAL TIKTOK DALAM DUNIA VIRTUAL - Sari, Okta Viana; Abidin, Sholihul (LPPM Universitas Putera Batam, 2024)
Social Media is a digital platform or website that facilitates interaction, information exchange, and content sharing among users online. The development of social media has transformed the way humans communicate and present themselves. Digital identity is an extension of physical self into virtual space, and platforms like TikTok provide a space to build and convey that identity. Self-identity refers to an individual's perception and understanding of who they are. The purpose of this research is to understand how the self-identity of Content Creator Dio Prayogi is presented on the front and backstage, as well as how Dio Prayogi engages in face-to-face interactions. Data collection techniques include in-depth interviews, observation, documentation, and literature review. The data analysis method utilizes the Miles and Huberman analysis model. The research findings on the self-identity of Content Creator Dio Prayogi reveal that on the front stage, Dio creates a more friendly atmosphere, utilizing humorous language, including jokes, banter, or funny language, often becoming key elements in Dio's speaking style. On the backstage, Dio Prayogi may be more authentic and reflect his personal side. Content creator Dio Prayogi employs interpersonal communication, including speaking style, word choice, and the way he interacts with his followers. Social Media is a digital platform or website that facilitates interaction, information exchange, and content sharing among users online. The development of social media has transformed the way humans communicate and present themselves. Digital identity is an extension of physical self into virtual space, and platforms like TikTok provide a space to build and convey that identity. Self-identity refers to an individual's perception and understanding of who they are. The purpose of this research is to understand how the self-identity of Content Creator Dio Prayogi is presented on the front and backstage, as well as how Dio Prayogi engages in face-to-face interactions. Data collection techniques include in-depth interviews, observation, documentation, and literature review. The data analysis method utilizes the Miles and Huberman analysis model. The research findings on the self-identity of Content Creator Dio Prayogi reveal that on the front stage, Dio creates a more friendly atmosphere, utilizing humorous language, including jokes, banter, or funny language, often becoming key elements in Dio's speaking style. On the backstage, Dio Prayogi may be more authentic and reflect his personal side. Content creator Dio Prayogi employs interpersonal communication, including speaking style, word choice, and the way he interacts with his followers.